Penilaian Kualitas Madu Berdasarkan Parameter Hidroksimetilfurfural, Total Padatan Terlarut, Dan Kadar Air Di Beberapa Apotek Kabupaten Pasar Kemis Tahun 2025: Tinjauan Klinis Terhadap Keamanan Konsumen: Tinjauan Klinis Terhadap Keamanan Konsumen - Gulsyaniraz Qadhi Zakka; Julia Totong (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2025)
Honey is a natural product used in therapy, but its quality is easily damaged by heat and poor storage. This study assessed HMF, moisture, and Total Dissolved Solids (TDS) in five honey brands across Pasar Kemis pharmacies. Results show all samples meet SNI standards, with HMF levels at 17,25–42,92 mg/kg and moisture at 13.59–18.93%. However, HMF variations indicate different levels of freshness. Clinically, high HMF may trigger oxidative stress and liver damage, especially in diabetics or patients with liver dysfunction. Pharmacists must act as gatekeepers (quality guardians) to ensure product integrity. It is recommended that pharmacists conduct routine stock monitoring and educate consumers to avoid overheating honey.